Multiple Roles of Glycans in Hematological Malignancies - Pang, Xingchen; Li, Hongjiao; Guan, Feng; Li, Xiang (Frontiers in Oncology, 2018)
The three types of blood cells (red blood cells for carrying oxygen, white blood cells for immune protection, and platelets for wound clotting) arise from hematopoietic stem/ progenitor cells in the adult bone marrow, and function in physiological regulation and communication with local microenvironments to maintain systemic homeostasis. Hematological malignancies are relatively uncommon malignant disorders derived from the two major blood cell lineages: myeloid (leukemia) and lymphoid (lymphoma). Malignant clones lose their regulatory mechanisms, resulting in production of a large number of dysfunctional cells and destruction of normal hematopoiesis. Glycans are one of the four major types of essential biological macromolecules, along with nucleic acids, proteins, and lipids. Major glycan subgroups are N-glycans, O-glycans, glycosaminoglycans, and glycosphingolipids. Aberrant expression of glycan structures, resulting from dysregulation of glycan-related genes, is associated with cancer development and progression in terms of cell signaling and communication, tumor cell dissociation and invasion, cell-matrix interactions, tumor angiogenesis, immune modulation, and metastasis formation. Aberrant glycan expression occurs in most hematological malignancies, notably acute myeloid leukemia, myeloproliferative neoplasms, and multiple myeloma, etc. Here, we review recent research advances regarding aberrant glycans, their related genes, and their roles in hematological malignancies. Our improved understanding of the mechanisms that underlie aberrant patterns of glycosylation will lead to development of novel, more effective therapeutic approaches targeted to hematological malignancies.